Analysis of the Application of Drill and Practice: Improve Business Letter Writing Skills - Rulita Nurfaizana, Della (Fakultas Ilmu Pendidikan Universitas PGRI Kanjuruhan Malang, 2024)
Students' ability to understand the concept of course topics is greatly influenced by the learning methods applied in class and each student's learning motivation. The right method will have a big influence on achieving learning outcomes. One learning method that can be used is the drill and practice method. This method is a teaching technique that involves student practice activities. With this method, students can develop dexterity and skills that are higher than those previously learned. The research method used in this research is the experimental method (pre-experimental design), where one class is used as an experimental class without a control class. This research design uses one group pretest-posttest. The research subjects consisted of 59 Office Administration Education students in the Bilingual Correspondence course at the Universitas Negeri Malang, even semester of the 2023/2024 academic year, taken from 2 (two) classes, namely Offering J and L. Based on analysis, the average student skill score during the pretest was 70 while the average post test score was 85. The results of the different test (one sample t-test) and the paired sample t-test showed a sig value of 0.000. This means that there is a significant difference in the pre-test results and post-test results and the Drill and Practice method has a significant effect on student skills.